On belonging and not belonging translation, migration, displacement - Jacobus, Mary (Princeton Princeton University Press, 2022)
"A look at how ideas of translation, migration, and displacement are embedded in the works of prominent artists, from Ovid to Tacita Dean"
"On Belonging and Not Belonging provides a sophisticated exploration of how themes of translation, migration, and displacement shape an astonishing range of artistic works. From the possibilities and limitations of translation addressed by Jhumpa Lahiri and David Malouf to the effects of shifting borders in the writings of Eugenio Montale, W. G. Sebald, Colm Tóibín, and many others, esteemed literary critic Mary Jacobus looks at the ways novelists, poets, photographers, and filmmakers revise narratives of language, identity, and exile. Jacobus's attentive readings of texts and images seek to answer the question: What does it mean to identify as-or with-an outsider? Walls and border-crossings, nomadic wanderings and Alpine walking, the urge to travel and the yearning for home-Jacobus braids together such threads in disparate times and geographies. She plumbs the experiences of Ovid in exile, Frankenstein's outcast Being, Elizabeth Bishop in Nova Scotia and Brazil, Walter Benjamin's Berlin childhood, and Sophocles's Antigone in the wilderness. Throughout, Jacobus trains her eye on issues of transformation and translocation; the traumas of partings, journeys, and returns; and confrontations with memory and the past. Focusing on human conditions both modern and timeless, On Belonging and Not Belonging offers a unique consideration of inclusion and exclusion in our world"--Provided by publisher.
Introduction: Unbelonging -- Identity poetics -- Of birds and men -- The coastal paradox -- Displaced persons -- Border crossing -- Re-wilding Antigone.
Includes bibliographical references and index.
Keywords: Translating and interpreting; Emigration and immigration in literature; Identity (Psychology) in literature; Assimilation (Sociology) in literature; Other (Philosophy) in literature; Electronic books